Interleukin-10 gene promoter polymorphism in patients with schizophrenia in a region of East Turkey - Ozbey, Ulku; Tug, Esra; Namli, Mustafa (Taylor & Francis Ltd, 2009)
Schizophrenia is one of the most severe psychiatric disorders, with a worldwide incidence of 1%. Immunological abnormalities have been found to be associated with schizophrenia for decades. Cytokines are key proteins involved in the immune system activation. Interleukin-10 (IL-10), an important immunoregulatory cytokine, is located on chromosome 1q31 32, a region previously reported to be linked to schizophrenia in genetic studies. In the present study it was aimed to examine the IL-10 gene promoter region's polymorphic variants in patients with schizophrenia in a population of the Elazig Region of East Anatolia, Turkey. Polymorphisms at position -1082, -819 and -592 in the IL-10 promoter region were determined in 171 Turkish patients who were diagnosed with schizophrenia, based on the DSM-IV, and 168 healthy controls, by polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP). We analyzed allele, genotype, and haplotype distributions using a case-control association study. Genotyping was performed by RFLP. Statistically significant differences were observed in both allelic and genotypic frequencies of the -592A/C polymorphism (Allele, P = 0.034, OR = 1.26, 95% CI 1.02 - 1.56; Genotype, P = 0.048), while the other two polymorphisms in distribution of the alleles and genotypes in patients with schizophrenia were not significantly different from those of controls (P > 0.05). Our results show a significant increase of GTA homozygotes (the high IL-10-producing haplotype) in schizophrenic patients compared to control subjects (P = 0.0001). These data suggest that the IL-10 gene promoter polymorphism may be one of the susceptibility factors to develop schizophrenia in the Turkish population, and apparently in all humans.
Keywords: Biological psychiatry; cytokines; genetics; polymorphism; schizophrenia